2014
DOI: 10.1002/app.40618
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evolution and properties of thermoplastic vulcanizate/organoclay nanocomposites

Abstract: Nanocomposites composed of organoclay and thermoplastic vulcanizates (TPVs) based on uncompatibilized or compatibilized polypropylene (PP)/ethylene–propylene–diene rubber (EPDM) blends were prepared in this study. The morphology of the nanocomposites was studied with wide‐angle X‐ray diffraction and transmission electron microscopy, which suggested that the addition of the compatibilizer played a key role in determining the morphology of the composites because of their interaction with the clay surface. Scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In comparison with the previously reported methods , EPDM rubber, EPDM‐ g ‐MA, and nanoclay were simultaneously fed into an internal mixer. After 2 min, PP was added and when constant torque was achieved, the curing agent was incorporated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the previously reported methods , EPDM rubber, EPDM‐ g ‐MA, and nanoclay were simultaneously fed into an internal mixer. After 2 min, PP was added and when constant torque was achieved, the curing agent was incorporated.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al showed that when nanoclay is added to EPDM in an internal mixer and then PP is added, the product has higher mechanical strength compared with products in which PP, EPDM, and clay are added simultaneously into the internal mixer , but they added the curing system into a mixture of PP and EPDM while mixing and did not use compatibilizer to disperse clay in the EPDM phase. Babu et al studied the effect of mixing sequence on peroxide cured TPV and reported that adding ethylene octane copolymer (EOC) curative masterbach to the molten PP yields higher mechanical properties .…”
Section: Introductionmentioning
confidence: 99%